2023
DOI: 10.1021/acs.est.2c07284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Temperature and Heavy Precipitation on Drinking Water Quality and Child Hand Contamination Levels in Rural Kenya

Abstract: Climate change may impact human health through the influence of weather on environmental transmission of diarrhea. Previous studies have found that high temperatures and heavy precipitation are associated with increased diarrhea prevalence, but the underlying causal mechanisms have not been tested and validated. We linked measurements of Escherichia coli in source water (n = 1673), stored drinking water (n = 9692), and hand rinses from children <2 years old (n = 2634) with publicly available gridded temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 101 publications
(206 reference statements)
0
9
0
Order By: Relevance
“…A previous study in Bangladesh found that safe storage of tubewell water in a container with a narrow mouth, tight-fitting lid and spigot significantly improved stored water quality and reduced diarrhea 34 . In a recent study in Kenya, heavy rainfall and extreme temperature were associated with increased E. coli in source water from boreholes, springs, and wells while heavy rainfall but not extreme temperature was associated with increased E. coli in stored drinking water 14 . In the same study, heavy rainfall did not increase stored water contamination among households that treated their water 14 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…A previous study in Bangladesh found that safe storage of tubewell water in a container with a narrow mouth, tight-fitting lid and spigot significantly improved stored water quality and reduced diarrhea 34 . In a recent study in Kenya, heavy rainfall and extreme temperature were associated with increased E. coli in source water from boreholes, springs, and wells while heavy rainfall but not extreme temperature was associated with increased E. coli in stored drinking water 14 . In the same study, heavy rainfall did not increase stored water contamination among households that treated their water 14 .…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study in Kenya, heavy rainfall and extreme temperature were associated with increased E. coli in source water from boreholes, springs, and wells while heavy rainfall but not extreme temperature was associated with increased E. coli in stored drinking water 14 . In the same study, heavy rainfall did not increase stored water contamination among households that treated their water 14 . Our findings suggest that treatment and safe storage of drinking water is especially important following extreme rainfall and temperature.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Temperature plays a critical role in shaping water quality parameters, exerting a significant influence on aquatic ecosystems and human health. Several studies have emphasized the intricate relationship between temperature and water quality indicators, highlighting the importance of understanding these dynamics in the context of climate change (Osman et al, 2024;Powers et al, 2023; Surface Water: The Importance of the Water Temperature, 2024; Water Science School, 2024).…”
Section: Impact Of Temperature On Water Quality Compared To Rainfallmentioning
confidence: 99%